Magnesium-aluminum mixed metal oxide supported copper nanoparticles as catalysts for water-gas shift reaction. (15th November 2016) - Li, Dalin; Cai, Yunbing; Chen, Chongqi; Lin, Xingyi; Jiang, Lilong
Graphical abstract: Highlights: Mg(Al)O supported Cu nanoparticles (1.5–5 nm) were obtained from Cu-Mg-Al LDHs. The WGS activity of the Cu catalysts increased with the increase of Cu 0 surface area. The highest Cu 0 surface area and WGS activity were achieved on 30%Cu/Mg2 Al. The optimized catalyst showed superior performance than commercial Cu/ZnO/Al2 O3 . Abstract: Mg(Al)O mixed metal oxide (MMO) supported Cu nanoparticles catalysts have been prepared by calcination and reduction of Cu-Mg-Al layered double hydroxides (LDHs). By adjusting the chemical compositions of LDHs precursors, various catalysts with 10–40 wt% Cu content and molar ratio of (Cu + Mg)/Al = 1–4 were prepared. The catalysts were characterized by ICP, N2 physical adsorption, XRD, TEM, H2 -TPR, and N2 O chemisorption, and tested for the water-gas shift (WGS) reaction. The characterization results suggested that upon calcination Cu-Mg-Al LDHs were converted to Mg(Cu, Al)O MMOs, where both Cu 2+ and Al 3+ were incorporated into the MgO framework to form a solid solution; reduction of Mg(Cu, Al)O gave highly dispersed and uniform Cu metal nanoparticles. The Cu metal dispersion was as high as 22–78% and the particle size varied from 1.5 to 5 nm depending on the chemical compositions. The WGS activity of the Cu catalysts increased with the increase of Cu 0 surface area. Among the prepared catalysts, the 30%Cu/Mg2 Al catalyst exhibited the highest Cu surface area and the highest WGS activity. The optimized catalyst also showed superior activity, thermal stability, and steady-state stability than a commercial Cu/ZnO/Al2 O3 catalyst under the present reaction conditions. The characterization on the spent catalysts showed that the LDHs-derived Cu nanoparticles remained highly dispersed, suggesting that the Mg(Al)O supported Cu nanoparticles were stable and possessed good resistance against sintering.